2010
DOI: 10.1002/hep.23592
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Lambda Genotype and Low Serum Low-Density Lipoprotein Cholesterol Levels in Patients With Chronic Hepatitis C Infection

Abstract: Recently, genetic polymorphisms occurring in the interferon (IFN)-lambda gene region were associated with response to IFN-based treatment of hepatitis C infection. Both infection with the hepatitis C virus and IFN therapy are associated with decreased serum cholesterol and high cholesterol has been associated with increased likelihood to respond to IFN. We sought to determine if the IFN-lambda gene variant was also associated with serum lipid levels in chronic hepatitis C patients. We compared genotypes of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
83
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 48 publications
13
83
0
Order By: Relevance
“…PEG-IFN/RBV), compared to those carrying the T allele (C/T and T/T genotypes). More recently, it has also been proposed that the poor response IL28B variants, in hepatitis C patients, are also associated with lower pretreatment low-density lipoprotein cholesterol levels, 17,18 hepatic steatosis, 18,19 and insulin resistance, 19 compared to the ''responder'' genotype. However, it is still unclear whether the genetic variation at the IL28B locus affects the severity and pace of the progression of liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…PEG-IFN/RBV), compared to those carrying the T allele (C/T and T/T genotypes). More recently, it has also been proposed that the poor response IL28B variants, in hepatitis C patients, are also associated with lower pretreatment low-density lipoprotein cholesterol levels, 17,18 hepatic steatosis, 18,19 and insulin resistance, 19 compared to the ''responder'' genotype. However, it is still unclear whether the genetic variation at the IL28B locus affects the severity and pace of the progression of liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have investigated the impact of IL28B host polymorphisms on lipid metabolism in patients with chronic HCV infection and noted an association of the responder genotype with higher levels of total cholesterol, apo-lipoprotein B, and low-density lipoprotein (LDL) [19]. In the context of liver transplantation, Eurich et al [20] have reported that rs8099917 influences the biochemical and histological levels of graft inflammation, though not the progression to fibrosis in patients with recurrent HCV infection post-transplant.…”
Section: Il28b Polymorphism and Clinical Features Of Chronic Hcv Infementioning
confidence: 99%
“…Due to the relatively small cohort, we were not able to demonstrate genotype-specific differences in baseline lathosterol levels and virologic response among cirrhotic patients. Other host variables such as IFNL3 gene variants have been associated with higher levels of LDL-C and ApoB for HCV GT1 but not GT3 [54]. However, there was no association between IFNL3 rs12979860 genotype with relapse in our cohort, and was not further evaluated in relation to sterol intermediates.…”
Section: Discussionmentioning
confidence: 64%